ALGORITHMIC BIAS AND THE RIGHT TO EQUALITY: REIMAGINING CONSTITUTIONAL GUARANTEES IN THE AGE OF ARTIFICIAL INTELLIGENCE - Mr. P.D. Sujith,; Dr. VR Dinkar, (IJRDO - Journal of Business Management, 2025)
Artificial Intelligence (AI) is transforming governance, employment, and legal systems. Yet, algorithmic bias, when AI systems systematically disadvantage certain groups poses a threat to the constitutional guarantee of equality. This paper investigates how AI can unintentionally reinforce discrimination, examines Indian constitutional provisions (Articles 14–18), and proposes a legal-ethical framework to ensure algorithmic accountability. Drawing on global best practices, the study suggests constitutional, statutory, and judicial reforms to balance innovation with justice